Formulation And Evaluation Of Xanthan Gum Based Extended Release Tablets Of Venlafaxine Hcl - Radke, R.S.; Hule, V.G.; Dhore, B.B.; M Ayaz, M Avez; Pagore, R.R. (Journal of Neonatal Surgery, 2024)
The present study aimed to formulate and evaluate Venlafaxine extended release matrix tablets using Xanthan gum as a natural release-retarding polymer. Extended release tablets were prepared by the wet granulation method using different concentrations of Xanthan gum to achieve sustained drug release. The prepared powder blends were evaluated for pre-compression parameters including angle of repose, bulk density, tapped density, Carr’s index, and Hausner ratio, which indicated good flow and compressibility characteristics suitable for tablet compression. The compressed tablets were further evaluated for post-compression parameters such as thickness, hardness, friability, weight variation, drug content, and swelling index. All formulations showed satisfactory physical characteristics within acceptable pharmacopeial limits. In vitro dissolution studies demonstrated that all formulations exhibited an initial burst release followed by sustained drug release behavior. The release rate decreased with increasing concentration of Xanthan gum due to the formation of a hydrophilic gel matrix that controlled drug diffusion and matrix erosion. Formulation F4 showed an optimized drug release profile with 18.42% drug release during the first hour and 97.62% cumulative drug release at the end of 12 hours. The optimized formulation exhibited satisfactory mechanical strength, good swelling behavior, and effective sustained release characteristics. The study concluded that Xanthan gum can be effectively utilized as a natural polymer for the development of extended release matrix tablets of Venlafaxine HCl with prolonged drug release and improved therapeutic performance